Examining the criterion-related validity of the Pervasive Developmental Disorder Behavior Inventory. (April 2015) - McMorris, Carly A; Perry, Adrienne
The Pervasive Developmental Disorder Behavior Inventory is a questionnaire designed to aid in the diagnosis of pervasive developmental disorders or autism spectrum disorders. The Pervasive Developmental Disorder Behavior Inventory assesses adaptive and maladaptive behaviors associated with pervasive developmental disorders and provides an age-standardized Autism Composite score. In previous research, the Pervasive Developmental Disorder Behavior Inventory has demonstrated moderate to strong reliability and validity. This study aimed to replicate and extend previous research by investigating the criterion-related validity of the Pervasive Developmental Disorder Behavior Inventory. Data from 40 children were analyzed in relation to other measures. The Pervasive Developmental Disorder Behavior Inventory adaptive scores were moderately correlated with cognitive and adaptive behavior scores as expected. However, no significant correlations were found between the maladaptive and Autism Composite scores of the Pervasive Developmental Disorder Behavior Inventory and the Childhood Autism Rating Scale. Results lead to concerns regarding the validity of some scores of the Pervasive Developmental Disorder Behavior Inventory.